Porosity Control and Transfer in Silicon Nanostructures through Electrochemical & Chemical Etching. (18th September 2015) - Defforge, Thomas; Vijayakumar, Sanahan; Loni, Armando; Chaix, Arnaud; Sauldubois, Audrey; Andreazza-Vignolle, Caroline; Cunin, Frédérique; Di Renzo, Francesco; Canham, Leigh T; Gautier, Gaël
Abstract : High surface area and controlled pore diameter silicon nanostructures were prepared using a two-step etching procedure. Firstly, the experimental conditions of silicon electrochemical etching leading to the formation of high surface area porous silicon thin films were described. Thereafter, the porous silicon layers were either lifted off the substrate to collect the porous particles or subjected to metal-assisted chemical etching (MaCE) in a hydrofluoric acid - silver nitrate solution to produce high aspect ratio porous silicon nanowires with controlled pore dimensions. The consecutive electrochemical and chemical (MaCE) silicon etching procedures enabled the synthesis of porous silicon nanowires with high specific surface area (up to 460 m²/g) along with low average pore diameter (below 6.5 nm).